Forty years of real-estate bubbles in the US and the macroeconomy: a Keynesian perspective - Herbert Walther (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2019)
This paper presents a dynamic, non-linear, stock–flow consistent aggregate Keynesian model with a banking sector, a household sector, a government sector, and a real-estate sector, to study the interactions between booms and busts in the real-estate sector and the macroeconomy. Using this model we try to simulate some 'stylized facts' about the US economy observable during the last four decades. It is argued that for various reasons house-price volatility in the US has increased since the 1980s: house prices seem to have followed a 'cobweb' pattern of accelerating instability, leading to the climax of the financial crises in 2007/2008. A new run-up of house prices has already started, pointing towards a looming bubble ahead. The US economy seems to have become addicted to asset-price bubbles as the driving force of the business cycle. It is argued that various institutional changes, which can be linked to the dominant economic ideology, are responsible for these developments.
Keywords: E12; E32; E52; E58; E62; 330; financial instability; real-estate price bubbles; business cycles